Association of prestroke metformin use, stroke severity, and thrombolysis outcome. (28th July 2020) - Westphal, Laura P.; Widmer, Roni; Held, Ulrike; Steigmiller, Klaus; Hametner, Christian; Ringleb, Peter; Curtze, Sami; Martinez-Majander, Nicolas; Tiainen, Marjaana; Nolte, Christian H.; Scheitz, Jan F.; Erdur, Hebun; et al.
Abstract : Objective: To evaluate whether pretreatment with metformin (MET) is associated with less stroke severity and better outcome after IV thrombolysis (IVT), we analyzed a cohort of 1, 919 patients with stroke with type 2 diabetes mellitus in a multicenter exploratory analysis. Methods: Data from patients with diabetes and ischemic stroke treated with IVT were collected within the European Thrombolysis in Ischemic Stroke Patients (TRISP) collaboration. We applied propensity score matching (PSM) to obtain balanced baseline characteristics of patients treated with and without MET. Results: Of 1, 919 patients with stroke with type 2 diabetes who underwent IVT, 757 (39%) had received MET before stroke (MET+), whereas 1, 162 (61%) had not (MET−). MET+ patients were younger with a male preponderance. Hypercholesterolemia and pretreatment with statins, antiplatelets, or antihypertensives were more common in the MET+ group. After PSM, the 2 groups were well balanced with respect to demographic and clinical aspects. Stroke severity on admission (NIH Stroke Scale 10.0 ± 6.7 vs 11.3 ± 6.5), 3-month degree of independence on modified Rankin Scale (2 [interquartile range (IQR) 1.0–4.0] vs 3 [IQR 1.0–4.0]), as well as mortality (12.5% vs 18%) were significantly lower in the MET+ group. The frequency of symptomatic intracerebral hemorrhages did not differ between groups. HbA1c levels were well-balanced between the groups. Conclusions: Patients with stroke and diabetes on treatment with MET receiving IVT had less severe strokes on admission and a better functional outcome at 3 months. This suggests a protective effect of MET resulting in less severe strokes as well as beneficial thrombolysis outcome.